"Analysis of the Effect of Gross Split Policies, Quality, and Price of Decisions on the Purchase of Domestic Operating Goods at PT. PHE ONWJ" - Dian Kumalasari, Elisabeth; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2019)
Abstract -  The Indonesian government has committed to creating a conducive investment climate in the oil and gas sub-sector to maintain domestic energy supply. However, the global challenge of reducing world oil prices has a direct impact on the decline in investment flows in the oil and gas sub-sector. In the past three years, upstream investment in the oil and gas sector has always been below the target. Beginning in 2017, Production Sharing Contracts between the Government and the Cooperation Contract Contractors (KKKS) that initially used the Cost Revovery scheme switched to the Gross Split scheme. The Gross Split scheme is expected to be able to make cashflow and contractor economics more attractive, so that it will encourage investment in the oil and gas sub-sector. In managing operating costs, KKKS with the Gross Split scheme will tend to be more careful and efficient in making decisions on purchasing operational goods because all operating costs incurred will be borne by the KKKS. The existence of information related to the quality and price of domestic operating goods that are less competitive is thought to be one of the factors that influence purchasing decisions, especially for KKKS with the Gross Split scheme.Keywords : investment, gross split, quality, price, decision.